Production Of Cellulase By Pycnoporus Sanguineus In Palm Oil Mill Effluent: Fermentation And Kinetic Studies - Kamaluddin, Fadzilah (2011)
Bioconversion of palm oil mill effluent (POME) is a novel approach in view of the increasing emphasis placed on sustainable and efficient industrial wastewater management. Biotechnological advances have seen the reuse of POME as a fermentation substrate for the production of various metabolites. In order to assess the potential of POME as substrate for cellulases production, nineteen microbial strains comprising of micro- and macrofungi were screened for cellulolytic activities. Pycnoporus sanguineus was found to be a potent producer of cellulases and laccase with maximum CMCase, FPase, β-glucosidase and laccase activities at 2.488, 1.405, 0.232 and 2.763 IU/mL, respectively.